If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) + 3 = 3x + 4 + -2x + 4 Reorder the terms: 2(6 + x) + 3 = 3x + 4 + -2x + 4 (6 * 2 + x * 2) + 3 = 3x + 4 + -2x + 4 (12 + 2x) + 3 = 3x + 4 + -2x + 4 Reorder the terms: 12 + 3 + 2x = 3x + 4 + -2x + 4 Combine like terms: 12 + 3 = 15 15 + 2x = 3x + 4 + -2x + 4 Reorder the terms: 15 + 2x = 4 + 4 + 3x + -2x Combine like terms: 4 + 4 = 8 15 + 2x = 8 + 3x + -2x Combine like terms: 3x + -2x = 1x 15 + 2x = 8 + 1x Solving 15 + 2x = 8 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 15 + 2x + -1x = 8 + 1x + -1x Combine like terms: 2x + -1x = 1x 15 + 1x = 8 + 1x + -1x Combine like terms: 1x + -1x = 0 15 + 1x = 8 + 0 15 + 1x = 8 Add '-15' to each side of the equation. 15 + -15 + 1x = 8 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = 8 + -15 1x = 8 + -15 Combine like terms: 8 + -15 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 84=w/6 | | 13.95d+1.95=85.65 | | n/8=-17 | | 6x(7x-8)-2(21x-6)=3-30x | | 13.95+1.95=85.65 | | (8+7)+(9+2)=18 | | v+-607=-907 | | (4x)(4x)-16x-9=0 | | 60000+80000=2x+x | | b/-1=-0.51 | | (x^3-2x+3)-(3x^2+4x-3)= | | g+99=-464 | | 184=2(w+20)+2w | | X^2+4=8-8 | | 7q=-602 | | -945=21b | | t+-165=-161 | | F(x)=2(x-7)(x-3) | | b/20=7 | | x^5+3x^4-4x^3+12x^2=0 | | 9j=99 | | p-15=21 | | -10z=50 | | 5x(3x-2)-15x(4+x)=140 | | X+(x+2)=(x+4)+31 | | (x^3-32)*2x= | | 2y=4(4-6) | | Kl=3x+4 | | x^2-4y^2+4x+24y-28=0 | | 3x-4x+6=5 | | k/16=0 | | 4x+y+130=0 |